How Should the Local Lighting Be Designed for a Mirror? An Investigation on the Preference of Users - Acari Erbil, Filiz; Dokuzer Ozturk, Leyla (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
The aim of this study is to investigate the preferred vertical illuminance in front of a mirror and luminaire placements for mirrors through experiments. For this purpose, a mirror was fixed on a wall of a mock-up room and three linear luminaires were placed around the mirror. Six lighting arrangements were designed using three luminaires around the mirror for local lighting and four indirect luminaires for general lighting in the room. Lighting scenarios were based on six different lighting arrangements and a range of vertical illuminances between 300 lx and 2000 lx. Surveys were conducted on the mirror lighting conditions in the homes of the participants as well as their impressions and preferences in terms of various lighting scenarios provided in the mock- up room. Findings obtained by means of the survey have been evaluated in terms of preferred vertical illuminance, emerging shadows and affected glare. Consequently, guiding criteria for mirror lighting were introduced.
Keywords: Vertical illuminance; mirror lighting; linear luminaire; shadow; glare; Architecture